Polyphyllin VII increases sensitivity to gefitinib by modulating the elevation of P21 in acquired gefitinib resistant non-small cell lung cancer - Honggang Wang; Zhenghua Fei; Hao Jiang (Elsevier, 2017)
Blockade of EGFR with reversible EGFR tyrosine kinase inhibitors (TKIs) is considered the frontline strategy for advanced NSCLC with EGFR mutations. However, acquired resistance to EGFR-TKI has been observed, resulting in disease progression and limited clinical benefit. Polyphyllin VII is the main member of polyphyllin family, which has been demonstrated to show strong anticancer activity against carcinomas. The sensitizing effect and underlying mechanism of Polyphyllin VII against acquired EGFR-TKI resistant NSCLC are still unexplored. In the present study, we aim to examined the sensitizing effect of Polyphyllin VII to gefitinib by modulating P21 signaling pathway in gefitinib acquired resistant NSCLC in vitro and in vivo. Gefitinib sensitive PC-9 cells and gefitinib acquired resistant H1975 cells were used. Cell proliferation and Clonogenic assay, Cell cycle analysis, Western blotting analysis and xenograft treatment were carried out. Polyphyllin VII enhanced the anti-proliferative effects of gefitinib and gefitinib-induced G1 phase arrest by modulation of P21 signaling pathway in acquired gefitinib resistant cells in vitro and in vivo. Polyphyllin VII elevated sensitization of gefitinib acquired resistant NSCLC cells to gefitinib through G1 phase arrest and modulation of P21 signaling pathway. It provides a potential new strategy to overcome gefitinib acquired resistance for EGFR-TKI resistant NSCLC.